PROSES KREATIF PEMBUATAN TOGOG TRADISIONAL DI MERTANING TOGOG ART GALLERY BALI: PROSES KREATIF PEMBUATAN TOGOG TRADISIONAL DI MERTANING TOGOG ART GALLERY BALI - Satrio Purwo Yudho; Suardina I Nyoman; Sumantra I Made (Pusat Penerbitan LPPM ISI Bali, 2026)
The creation of this work aims to explore figurative forms in the art of paras stone sculpture and develop sculptural techniques that are efficient and have high aesthetic value while still being based on Balinese traditions. Through this work, the author seeks to present figures that have a strong visual character and are full of symbolic meaning, so that they can represent the spiritual values and local wisdom of the Balinese people. The creation method used refers to the Sp. Gustami method, which consists of three main stages, namely exploration, design, and realization. The exploration stage is carried out by exploring ideas and references from traditional Balinese cultural sources and iconography. The design stage includes sketching, determining anatomical proportions, and making an initial model. Meanwhile, the embodiment stage is realized through the process of manual level stone carving, including the formation of bare, refining, and finishing. The result of the creation produced five sculptures with the figures of Rsi, Delem, the Suratma, the Head of the Buddha, and the Cow, each with its own characteristics and symbolic meaning. Each work highlights a blend of technique, expression, and philosophy, thus bringing strong aesthetic value and spiritual depth. In conclusion, this creation shows that traditional Balinese sculpture art is still very relevant to be developed as a medium of artistic expression and cultural preservation. Through the exploration of form and the application of proper sculptural techniques, the work of the paras stone sculpture is not only an aesthetic representation, but also a container for the inheritance of the noble values and spirituality of the Balinese people.